-z=6z-5

Simple and best practice solution for -z=6z-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -z=6z-5 equation:


Simplifying
-1z = 6z + -5

Reorder the terms:
-1z = -5 + 6z

Solving
-1z = -5 + 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
-1z + -6z = -5 + 6z + -6z

Combine like terms: -1z + -6z = -7z
-7z = -5 + 6z + -6z

Combine like terms: 6z + -6z = 0
-7z = -5 + 0
-7z = -5

Divide each side by '-7'.
z = 0.7142857143

Simplifying
z = 0.7142857143

See similar equations:

| 6d-5=25 | | (7-u)(3u+8)=0 | | -2x-13=9x+9 | | 1/2x27x24 | | x^2+6xy+8y^2=0 | | 100x=7(24.99) | | (3+5)*(14-9)= | | 100x=5.5(125) | | 100x=6(95) | | (3+5)x(14-9)= | | L=3W-11 | | L=3W-5 | | 98.6x=-34.6(100) | | 3/5(4x+7)=3(1-2x)+18 | | 128x=8(100) | | 25x=15(100) | | 0.50x+0.25(30)=25.5 | | 5x^2+5x+6=0 | | x^3+-4x^2+-45x=0 | | 3x=-18+2 | | x^3-4x^2-45=0 | | 2x+7=2(x-5) | | (4y+2)(7+y)=0 | | -4x+5=x-10 | | 3-6(8-4)= | | -x^2+-13x-40=0 | | (x2-24x2)3/4 | | 3(-8)+5y=-59 | | x^2-13x+-40=0 | | 1/t+1/3t=1/2 | | 4(15)-3y=51 | | 2w^2+11w+23-2w^2-10w-25=0 |

Equations solver categories